Chapter Regulation of the G1/S Transition in Adult Liver: Expression and Activation of the Cyclin Dependent Kinase Cdk1 in Differentiated Hepatocytes is Controlled by Extracellular Signals and is Crucial for Commitment to DNA Replication - Pascal, Loyer; Anne, Corlu (InTechOpen, 2021)
Electronics engineering